Keeping found things found the study and practice of personal information management - Jones, William P., 1952- (Amsterdam ; Boston : Morgan Kaufmann Publishers, 2008)
WE ARE ADRIFT IN A SEA OF INFORMATION. We need information to make good decisions, to get things done, to learn, and to gain better mastery of the world around us. But we do not always have good control of our information - not even in the "home waters" of an office or on the hard drive of a computer. Instead, information may be controlling us - keeping us from doing the things we need to do, getting us to waste money and precious time. The growth of available information, plus the technologies for its creation, storage, retrieval, distribution and use, is astonishing and sometimes bewildering. Can there be a similar growth in our understanding for how best to manage information and informational tools? This book provides a comprehensive overview of personal information management (PIM) as both a study and a practice of the activities people do and need to be doing so that information can work for them in their daily lives. Introductory chapters of Keeping Found Things Found: The Study and Practice of Personal Information Management provide an overview of PIM and a sense for its many facets. The next chapters look more closely at the essential challenges of PIM, including finding, keeping, organizing, maintaining, managing privacy, and managing information flow. The book also contains chapters on search, email, mobile PIM, web-based support, and other technologies relevant to PIM. * Focuses exclusively on one of the most interesting and challenging problems in today's world * Explores what good and better PIM looks like, and how to measure improvements * Presents key questions to consider when evaluating any new PIM informational tools or systems.
Foundations. A study and a practice ; A personal space of information ; A framework for personal information management -- Activities. Finding and re-finding: from need to information ; Keeping and organizing: from information to need ; Maintaining for now and for later ; Managing privacy and the flow of information ; Measuring and evaluating ; Making sense of things -- Solutions. Email disappears? ; Search gets personal ; PIM on the go ; PIM on the Web -- Conclusions. Bringing the pieces together ; Finding our way in(to) the future.
Includes bibliographical references (p. 403-421) and index.
Keywords: Personal information management; Information retrieval; Privacy; Electronic books